2014
DOI: 10.1016/j.neuron.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Epigenetic Modification Regulates Stochastic Expression of Clustered Protocadherin Genes, Generating Single Neuron Diversity

Abstract: In the brain, enormous numbers of neurons have functional individuality and distinct circuit specificities. Clustered Protocadherins (Pcdhs), diversified cell-surface proteins, are stochastically expressed by alternative promoter choice and affect dendritic arborization in individual neurons. Here we found that the Pcdh promoters are differentially methylated by the de novo DNA methyltransferase Dnmt3b during early embryogenesis. To determine this methylation's role in neurons, we produced chimeric mice from D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 61 publications
(93 reference statements)
12
150
2
Order By: Relevance
“…S4A). The Pcdha cluster contains 14 variable exons, each regulated by its own promoter, followed by three constant exons, and is highly expressed in neurons (38). Except for Pcdha8 and Pcdhac2, expression of all genes in the Pcdha cluster was dramatically downregulated in Tet3 KO mESCs on day 6 of SFEB culture relative to WT control cells (Fig.…”
Section: Tet3 Influences the Expression And Dna Modification Status Omentioning
confidence: 97%
“…S4A). The Pcdha cluster contains 14 variable exons, each regulated by its own promoter, followed by three constant exons, and is highly expressed in neurons (38). Except for Pcdha8 and Pcdhac2, expression of all genes in the Pcdha cluster was dramatically downregulated in Tet3 KO mESCs on day 6 of SFEB culture relative to WT control cells (Fig.…”
Section: Tet3 Influences the Expression And Dna Modification Status Omentioning
confidence: 97%
“…For Pcdhs, expression of each variable exon is controlled by its upstream promoter (Tasic et al 2002, Toyoda et al 2014, Wang et al 2002a). Together, these findings support a model in which selection of alternative exons (Dscam1s) or promoters (Pcdhs) is stochastic, making it likely that individual neurons express unique sets of isoforms on their cell surface.…”
Section: Figurementioning
confidence: 99%
“…74 A separate study also identified an interaction between TFII-I and DNMT3B in iPSCs. 61 Interestingly, both the PCDH cluster and DPP6 were shown to undergo DNMT3B-mediated methylation, 75,76 and so it is possible that gene dosage of GTF2I might be involved in the DM profiles we detected at these loci. TFII-I has also been shown to bind to the promoter region of EZH2, encoding a member of the polycomb repressive complex 2 (PRC2), in embryonic stem cells, 77 which is the same cell type in which we observed enrichment of EZH2 binding sites and regions containing H3K27me3-marked chromatin, a characteristic of transcriptional silencing by PRC2, within DM probes.…”
Section: Discussionmentioning
confidence: 94%